Code Mixing Used in Deddy Corbuzier’s YouTube Video Podcast - Nurochman Nurochman; Suardi Suardi; Hendro Prabowo (Asosiasi Dosen Muda Indonesia, 2026)
This study analyzed the phenomenon of code mixing in the realm of Indonesian digital media, particularly in podcast content on YouTube. The study focused on the use of code mixing by Deddy Corbuzier, a prominent YouTuber and podcast host, in one episode of the “Close the Door” segment featuring Cinta Laura Kiehl. Using a qualitative descriptive approach, the data were obtained through careful transcription of the conversation and systematic identification of code-mixing instances. The analysis was conducted by referring to Suwito’s (1985) theory of code-mixing form classification and Hoffman’s (1991) theory of motives. The results indicate that there are 110 instances of code mixing, with clause forms (39%) and word forms (35%) being the most dominant types. Meanwhile, the primary motive for code-mixing usage is expressing group identity (56%), followed by discussing particular topics (19%). These findings reveal that code mixing in Deddy Corbuzier’s podcast functions not only as a pragmatic communication tool but also as a sociolinguistic strategy to build closeness with young audiences (Gen Z and millennials) who are multilingual, as well as to assert a modern and global identity within contemporary digital media discourse